Wytwarzanie energii poetyckiej. Casus Ut pictura poesis Witolda Wirpszy - Bogalecki, Piotr (Przestrzenie Teorii, 2024)
The article proposes an interpretation of an unpublished poem by Witold Wirpsza, Ut pictura poesis, discovered in the Archives of the Academy of Fine Arts in Berlin. Analysis of the poem makes it possible to distinguish two basic thematic lines in its structure: philosophical-logical (due to references to L. Wittgenstein’s Tractatus Logico-Philosophicus) and comparative-aesthetic (due to the presence of the title topos ut pictura poesis and ironic ekphrasis of the sculptures of A. Rodin). The reflection on “the production of poetic energy” present in the poem is interpreted in light of Wirpsza’s essays on energy and cybernetics, his unpublished diaries and his reception of T. Peiper’s theory of poetry, especially the diary notes from 1981. Written most likely in the late period, the poem “Ut pictura poesis” may appear as a kind of artistic summary of several important themes in Wirpsza’s poetry.